An Audit Of The Referral Letter Received At Klinik Pakar Orthodontik Jln Abd Samad - Mohamed Zini, Suryati Hartini; Nordin, Nisreen (IIUM Medical Journal Malaysia, 2017)
Introduction: The objectives of this study were to determine the prevalence and the pattern of hypodontia among orthodontic patients in Klinik Pergigian Jalan Sultan Mahmud, Kuala Terengganu. Materials and Methods: This was a retrospective study where 351 orthodontic patients records (comprises of 104 males and 247 females), were reviewed. The records were evaluated by a trained dental officer between October 2016 and June 2017. The Chi-square and Fisher’s Exact Tests were carried out for statistical analysis. Results: The prevalence of hypodontia was 10.8%. Thirty-eight (38) patients were found to have at least a single missing tooth. A significant difference was found between males and females having hypodontia (p = 0.048). No significant difference was found for hypodontia patients by races (p = 0.829). The maxillary lateral incisor was the most frequently missing tooth followed by mandibular second premolar and mandibular lateral incisor. Hypodontia cases observed, tended to be more likely occurred in the upper left arch compared to the lower arch. The majority of hypodontia patients had a single missing tooth, but rarely more than 3 missing teeth. Hypodontia patients had mainly Class III malocclusion, however no statistically significant difference was found (p = 0.081). Conclusion(s): The prevalence of hypodontia of this study was within the range of what is being reported in the literature and showed gender significant. In this sample, hypodontia mainly involved maxillary lateral incisors; more prevalent in the upper arch; and mostly observed in patients with Class III malocclusion. Early detection and accurate diagnosis are essential. Therefore, alternative treatment modalities can be well planned under multidisciplinary team approach in restoring the aesthetic and function.